2021
DOI: 10.1111/ruso.12383
|View full text |Cite
|
Sign up to set email alerts
|

Watching Together: Local Media and Rural Civic Engagement*

Abstract: Civic engagement involves active participation in political and nonpolitical contexts in one's community. Research consistently demonstrates that sociodemographic factors, neighborhood context, community size, and media use are all important antecedents of robust civic engagement. This paper focuses on the intersection between these latter two factors. My paper draws on multiple streams of research in the rural sociology and communication literature to develop a theoretical framework where rural individuals' u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 71 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…Finally, religiosity—especially evangelism—tends to be higher in rural areas, which also corresponds with higher rates of political participation and social capital (Putnam 2000; Putnam et al 2010). That said, rural areas may be behind urban areas in terms of participation rates due to a declining local media market, which is a key component of civic engagement (Thompson 2021).…”
Section: Potential Differences In Urban-rural Political Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, religiosity—especially evangelism—tends to be higher in rural areas, which also corresponds with higher rates of political participation and social capital (Putnam 2000; Putnam et al 2010). That said, rural areas may be behind urban areas in terms of participation rates due to a declining local media market, which is a key component of civic engagement (Thompson 2021).…”
Section: Potential Differences In Urban-rural Political Participationmentioning
confidence: 99%
“…Once again, rural (or urban) attitudes would have less of an impact on politics if various elements of participation lag among that group. Although there is a gap in the literature comparing urban-rural participation rates in recent years, a few studies have looked at either urban-rural differences in political participation rates from over a decade ago (Kaufman, 2019a) or have focused on rural participation rates without controlling for other factors (Thompson, 2021). In the former study, participation rates of rural areas have been found to be lower than those of urban areas generally.…”
Section: Potential Differences In Urban-rural Political Participationmentioning
confidence: 99%
“…In a general sense, participation means "the act of taking part in an event or activity" [30]. In the social sciences, this concept is applied to political engagement (e.g., participation in elections) and non-political activity [31] (p. 940), [24,32]. In short, participation can be defined as "a process in which individuals take part in decision making in the institutions, programs and environments that affect them" [33] or "the engagement of individuals with the various structures and institutions of democracy" [34] (p. 4).…”
Section: Theoretical Background 21 the Concept Of Participationmentioning
confidence: 99%
“…In the case of participation in social consultations, attachment to the place of residence and the individual's religiosity are crucial [58] (pp. [74][75], [31] (p. 938).…”
Section: Public and Social Participation In Polish Societymentioning
confidence: 99%
“…However, internet platforms and social media, such as, Twitter are crucial for communication among producers who live farther away from each other. In their studies on knowledge exchange regarding sustainable soil management for producers in the European Union, Mills et al (2019) found that Twitter is efficient in spreading information, while Thompson (2021) concluded that local media are important for rural Americans to obtain local news and information to participate in local activities.…”
Section: Introductionmentioning
confidence: 99%